Structural features of two pyridyl compounds of 1,5-Bis-(2′-pyridyl)pentane-1,3,5-trione and a new salt of doubly protonated Hydroxyterpyridinium - Momeni, Badri Z.; Fathi, Nastaran; Rahimi, Farzaneh; Rominger, Frank (Journal of chemical crystallography, 2020)
A keto-enol equilibrium between two tautomers of the 1,5-bis(2′-pyridyl)pentane-1,3,5-trione (trione) (1) was observed in solution based on 1H and 13C NMR spectroscopy. NMR data shows that the trione exists as a mixture of mono-(minor product) and bis-enolic (major product) forms in solution. However, the crystal structure of trione (1) indicates that the bisenolic form is the predominant species in the solid state, which is probably due to the C=O⋯H-O intramolecular hydrogen bonding. The crystal structure of 1 was determined by X-ray diffraction analysis. Trione (1) is monoclinic and crystallizes in the space group P 21/n with a = 3.7449(3) Å, b = 29.594(3) Å, c = 12.5148(12) Å, ß = 92.701(2)°. Notably, the chloride salt of doubly protonated 4′-hydroxy-2,2′:6′,2″-terpyridinium [H2(tpyOH)]Cl2·H2O (tpyOH = 4′-hydroxy-2,2′:6′,2″-terpyridine) (2) obtained during the reaction of tpyOH in the presence of CrCl3·6H2O as a Lewis acid in methanol rather than complexation. The crystal structure of [ H2(tpyOH)]Cl2·H2O (2) is triclinic and crystallizes in the space group P1̄ with a = 5.1169(15) Å, b = 12.288(4) Å, c = 13.212(4) Å, α = 109.667(7)°, ß = 100.321(7)°, γ = 94.111(7)°. The crystal structure of 2 reveals the protonation of two nitrogen atoms of outer pyridines in tpyOH to form the [ H2(tpyOH)]2+ cation. The packing of [ H2tpyOH] Cl2·H2O features weak interactions including three N-H⋯Cl, O-H⋯Cl and O-H⋯O hydrogen bonds and extensive hydrogen bonds due to the cis-cis conformation of the doubly protonated salt of [ H2tpyOH]2+ cation.